Effect of Organic Matter vis-a-vis Humic Acid on Nutrient Availability and Yield Attributes of Rice – Mustard Cropping Sequence - Utpal Giri; Dipankar Saha, Niladri Paul, Ashim Datta (Journal of the Indian Society of Soil Science, 2017)
The influence of organic matter vis-a-vis humic acid on nutrient availability and its impact on rice (var MTU 1010) followed by mustard (var B-9), were studied in Typic Fluvaquent soil under old alluvial zone of India. Soil is sandy clay loam, having C/N ratio of 8.29, available phosphorus (P) 25.9 kg ha-1, available potassium (K) 127.4 kg ha-1, and available sulphur (S) 39.5 kg ha-1, respectively. The C:N ratio of the added farmyard manure (FYM), commercial and FYM extracted humic acid were 32.1, 32.6, 13.5, respectively. Experimental soil received recommended doses of fertilizers for cultivation of rice (N:P2O5:K2O::60:30:30) followed by mustard (80:40:40) along with FYM at 10.0 and 5.0 t ha-1, commercial humic acid at 1.0, 0.5 kg ha-1 and FYM extracted humic acid at 1.0, 0.5 kg ha-1, respectively as per treatment combinations, following randomized block design (RBD). Rhizosphere soil (0-15 cm) and plant samples were periodically collected and analyzed for available P, K and S to find their integral effects on crop growth. At panicle initiation and branching stages of rice and mustard, available P, K and S recorded highest values, thereafter gradually decline towards harvesting stage. The FYM extracted humic acid resulted in highest availability of P, K and S, whereas commercial humic acid enhanced the content of K in rice, which signified uptake of nutrients within plants resulted qualitative enrichment through biometric parameters and yield of rice and mustard.